Pengembangan Karir, Work-Family Conflict, dan Kecerdasan Emosional pada Kinerja Perawat Wanita di Ruang Rawat Inap dan Rawat Jalan - Tallupadang, Resty; Nurwijayanti, Nurwijayanti; Ellina, Agusta Dian (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
One of the most pressing needs in hospitals is for qualified nurses, with the majority of nurses being female. However, the public often complains about the quality of health services provided by nurses, particularly female nurses. The main issue for health service users, especially in hospitals, is the performance of nurses. According to the management of the nursing section and the head of Torabelo Regional Hospital in Sigi Regency, this is influenced by several factors, including a lack of career development, work-family conflict (which is the most frequent occurrence), and a lack of emotional intelligence among female nurses. This research aims to determine the impact of career development, work-family conflict, and emotional intelligence on the performance of female nurses, both individually and collectively, in the inpatient and outpatient rooms at Torabelo Regional Hospital in Sigi Regency. This is a quantitative research study that uses a causal associative research design. The study focuses on female nurses, who have worked for at least 2 years and have either civil servant or contract status. The primary data was collected using a questionnaire with a Likert scale, while secondary data was obtained from nursing management. The data analysis involved using Spearman rank analysis and linear regression analysis to determine the impact of career development, work-family conflict, and emotional intelligence on the performance of female nurses. From a sample of 82 female nurses, the results showed that career development had a positive and significant effect on the performance of female nurses (p=0.001, α=0.349), work-family conflict had a negative and significant effect on the performance of female nurses (p=0.039, α=-0.215), emotional intelligence has a positive and significant effect on the performance of female nurses (p=0.000, α=0.663), and simultaneously career development,work-family conflict, and emotional intelligence influence the performance of female nurses (p=0.000, α=43.952).